KOSTUM PERTUNJUKAN WAYANG ORANG SERIAL MAHABARATA GAYA SURAKARTA - Indri Hapsari; Donie Fadjar Kurniawan (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2021)
This reseach is based on the variety interpretations on the human puppet show on the mahabarata story in Indonesia. These various interpretations produce a lot of style and one of them is Surakarta style.The interpretation of Surakarta style can be observed by the dancer’s costume which have the uniquecharacteristic adapted by local tradition.The goal of this research is to make a deep and detail data in the using of mahabarata’s dancer costume in Surakarta style. The method used in this research is qualitative descriptive. The subjects of the research are Mahabarata’s human puppet show in Sriwedari, Indonesian Institute of The Arts (ISI) Surakarta, and Taman Budaya Jawa Tengah (TBJT) Surakarta. The steps in thisresearch are literature review, data collection and draw conclusion. The conclusion is The use of the puppet costume of the mahabarata series, Surakarta style was adjusted to the characteristics of the puppet figures and plays performed. Costume design is the result of visualization of fashion on the human puppet show. Thesuggestion of this research can be used as the reference in the mahabarata’s dancer costume of Surakarta style and provide the knoeledge contribution as an effort to preserve human puppet in Surakarta style.